1894 S.C. Rev. Stat. 307, tit. 2, ch. 9, § 129 (enacted 1880) - (:unkn) unknown (My University, 1880)
Prohibited the carrying of a concealed pistol, dirk, dagger, slungshot, metal knuckles, razor, or other deadly weapon. Punishable by fine up to $200 and/or imprisonment up to 1 year.
Keywords: CARRY - CONCEALED